‘Revenge porn’ and women empowerment issues: implications for human rights and social work practice in Zimbabwe - Mafa, Itai; Kang’ethe, Simon; Chikadzi, Victor (Springer Science+Business Media B.V., 2021)
Although the issue of revenge porn dates back before the popularization of social media, concerns over its gender bias and other adverse concomitant ramifications have recently attracted attention from a human rights perspective. While it has been widely acknowledged that women subjugation through revenge porn is a reality in Zimbabwe, this has not been met with the radical policy reformations that the challenge demands. Using a qualitative approach, this paper explored the dynamics surrounding revenge porn as a phenomenon thwarting the efforts of women-NGOs in their fight against gender inequality and women exclusion. The paper underscores the urgent need to enact laws that would provide a clear legal and policy framework for dealing with revenge porn in Zimbabwe.